Detection of rare G3P[19] porcine rotavirus strains in Chiang Mai, Thailand, provides evidence for origin of the VP4 genes of Mc323 and Mc345 human rotaviruses - Maneekarn N. (2014)
Among 175 fecal specimens collected from diarrheic piglets during a surveillance of porcine rotavirus (PoRV) strains in Chiang Mai, Thailand, 39 (22.3%) were positive for group A rotaviruses. Of these, 33.3% (13 of 39) belonged to G3P[19], which was a rare P genotype seldom reported. Interestingly, their VP4 nucleotide sequences were most closely related to human P[19] strains (Mc323 and Mc345) isolated in 1989 from the same geographical area where these PoRV strains were isolated. These P[19] PoRV strains were also closely related to another human P[19] strain (RMC321), isolated from India in 1990. The VP4 sequence identities with human P[19] were 95.4% to 97.4%, while those to a porcine P[19] strain (4F) were only 87.6 to 89.1%. Phylogenetic analysis of the VP4 gene revealed that PoRV P[19] strains clustered with human P[19] strains in a monophyletic branch separated from strain 4F. Analysis of the VP7 gene confirmed that these strains belonged to the G3 genotype and shared 97.7% to 98.3% nucleotide identities with other G3 PoRV strains circulating in the regions. This close genetic relationship was also reflected in the phylogenetic analysis of their VP7 genes. Altogether, the findings provided peculiar evidence that supported the porcine origin of VP4 genes of Mc323 and Mc345 human rotaviruses. Copyright © 2006, American Society for Microbiology. All Rights Reserved.